Impact of Land Conversion on Agricultural Carrying Capacity and LP2B in Sleman Regency - Harini, Rika; Ariani, Rina Dwi; Kuncoro, Aflah Bening; Buana, Adam Satria; Puspitaningrum, Ismi Nuari (Universitas Negeri Medan, 2025)
Land conversion is frequent in rural and urban areas where an increase in population is directly connected to the growing demand for additional land. A region with the highest rate of land conversion is Sleman Regency which is among the 3 regencies in the Special Region of Yogyakarta. Therefore, this study aimed to examine conversion of agricultural land to determine the qualification as sustainable and how the resources could be relocated for other uses. The analysis was conducted quantitatively and descriptively using secondary data from a time series database spanning 2015 to 2020. The results were presented through a combination of tables, graphs, images, and map visualizations. The study further showed that 4.412 hectares of agricultural land experienced a functional change over 5 years with the most significant change occurring in Pakem Subdistrict (1.540 hectares) and the least in Kalasan Subdistrict (4 hectares). Carrying capacity value of agricultural land in Moyudan, Godean, Cangkringan, Minggir, Seyegan, Ngaglik, Mlati, Prambanan, and Ngemplak was also influenced by the quantity of agricultural land available in each subdistrict. A maximum carrying capacity showed that adequate food was produced to sustain the population. Conversely, Depok and Turi Subdistricts possessed the lowest land-carrying capacity, showing that the subdistricts depended on food production to meet the population’s needs.